Residual C-peptide secretion and hypoglycemia awareness in people with type 1 diabetes - Giesje Nefs; Bruce H R Wolffenbuttel; Peter R van Dijk; Petronella H Geelhoed-Duijvestijn; Henk-Jan Aanstoot; Martine J Wellens; Charlotte E Vollenbrock; Pim Dekker; Lianne S M Boesten; Martine M C de Vries-Velraeds (BMJ Open Diabetes Research & Care, 2021)
Introduction This study aimed to assess the association between fasting serum C-peptide levels and the presence of impaired awareness of hypoglycemia (IAH) in people with type 1 diabetes.Research design and methods We performed a cross-sectional study among 509 individuals with type 1 diabetes (diabetes duration 5–65 years). Extensive clinical data and fasting serum C-peptide concentrations were collected and related to the presence or absence of IAH, which was evaluated using the validated Dutch version of the Clarke questionnaire. A multivariable logistic regression model was constructed to investigate the association of C-peptide and other clinical variables with IAH.Results In 129 (25%) individuals, residual C-peptide secretion was detected, while 75 (15%) individuals reported IAH. The median (IQR) C-peptide concentration among all participants was 0.0 (0.0–3.9) pmol/L. The prevalence of severe hypoglycemia was lower in people with demonstrable C-peptide versus those with absent C-peptide (30% vs 41%, p=0.025). Individuals with IAH were older, had longer diabetes duration, more frequently had macrovascular and microvascular complications, and more often used antihypertensive drugs, antiplatelet agents and cholesterol-lowering medication. There was a strong association between IAH and having a severe hypoglycemia in the preceding year. In multivariable regression analysis, residual C-peptide, either continuously or dichotomous, was associated with lower prevalence of IAH (p=0.040–0.042), while age at diabetes onset (p=0.001), presence of microvascular complications (p=0.003) and body mass index (BMI) (p=0.003) were also independently associated with the presence of IAH.Conclusions Higher BMI, the presence of microvascular complications and higher age at diabetes onset were independent risk factors for IAH in people with type 1 diabetes, while residual C-peptide secretion was associated with lower risk of this complication.